Automatic information processing bias to stress factors by older adults with and without diabetes - Hernández Cortés, Perla Lizeth; López Ramírez, Ernesto Octavio; Morales Martínez, Guadalupe Elizabeth; Salazar González, Bertha Cecilia (U.S. G.P.O., 2014)
A sample of 65 older adults (with and without diabetes) as well as a sample of 84 healthy young people were required to take affective priming studies to compare recognition latencies of stress related word pairs against recognition latencies of positive, negative and neutral word pairs. Moreover, older adults took a stress questionnaire related to relevant disturbing events in the third age. The goal was to test any automatic emotional processing bias to these events. Results suggested that even when people with diabetes obtained low stress test scores, they showed automatic cognitive bias to process stressful events differently than older adults without diabetes and young people. This suggested that people with diabetes patients’ controlled strategies to cope with stress might not be aware of such an automatic cognitive bias. It is argued that this information processing style to stressful events makes patients prone to cognitive emotional vulnerability.